Comparison of closed and open reduction in developmental hip dysplasia regarding leg inequality - Gurger, Murat (Bayrakol Medical Publisher, 2019)
Aim: The aim of our study is to identify and compare the characteristics of leg length discrepancy in unilateral developmental hip dysplasia patients treated with closed reduction and medial open reduction. Material and Method: Clinical and radiographic data of 108 patients with unilateral developmental hip dysplasia were evaluated retrospectively. Thus, 31 patients (42.5%) were included in closed reduction group (Group 1), and 42 patients (57.5%) were included in the medial open reduction group (Group 2). The mean age of the patients at the time of the treatment in Group 1 was 9.9 +/- 4.5 months, and the mean age of the patients in Group 2 was 12.8 +/- 5.5 months. Radiography scans were obtained by computed radiography to assess radiological parameters of patients during the final examination. Results: The results showed that both differences in length in Group 1 and Group 2 were mainly due to the femur. Mean extremity length difference of patients in the closed reduction group was close to the difference seen In the normal population. In the group with medial open reduction, a greater difference was found and this difference was statistically significant when compared regarding leg length discrepancy in patients in Group 1 and Group 2. Discussion: In our study, we noticed that in most of our patients, leg length difference was not clinically significant, but in some patients, this difference was approximately two cm. Therefore, we recommend that the patients especially undergoing medial open reduction should be followed for leg length inequality until their skeletal maturity is reached.
Keywords: Leg Length Inequality; Hip Dislocation; Congenital